Cross-checking optimal monetary policy with information from the Taylor rule - Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper shows that monetary policy should be delegated to a central bank that cross-checks optimal policy with information from the Taylor rule. Attaching some weight to deviations of the interest rate from the interest rate prescribed by the Taylor rule is beneficial if the central bank aims at optimally stabilizing inflation and output gap variability under discretion. Placing a weight on deviations from a simple Taylor rule increases the overall relative weight of inflation volatility in the effective loss function, which reduces the stabilization bias of discretionary monetary policy. The welfare-enhancing role of this modified loss function depends on the size of the stabilization bias, i.e. on the degree of persistence in the cost-push shock process, and the relevance of demand shocks. These results can be interpreted in terms of the optimal composition of monetary policy committees.
Keywords: E43; E52; 330; optimal monetary policy; stabilization bias; monetary policy delegation; robustness; Taylor rule; monetary policy committee; Geldpolitik; Taylor-Regel; Diskretionäre Politik; Konjunkturpolitik; Inflation; Volatilität; Wohlfahrtseffekt; Theorie